An Analysis of High School Students’ Understanding Ability of Mathematical Concepts in Online Learning During the Pandemic - Rahmania, Messa Dwi; Pujiastuti, Heni (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The purpose of this research is to determine the level of students’ understanding ability of mathematical concepts at the high school level who carry out full online learning during the pandemic. The type of research used is the descriptive research method with a qualitative approach. The subjects used as samples were 3 students. The sampling technique used is the purposive sampling technique. In order to achieve the research objectives, the instruments prepared were test instruments related to the problem of understanding mathematical concepts which were then presented to subjects who were doing full online learning during the pandemic. Based on the results of research that has been carried out, it is known that the level of ability to understand mathematical concepts of students at the high school level who are doing full online learning during the pandemic is classified as good, and no decline has been detected, this is evidenced by the results of the answers carried out by the 3 subjects in test instruments that have been presented